2012
DOI: 10.1161/strokeaha.112.666461
|View full text |Cite
|
Sign up to set email alerts
|

Silent Stroke

Abstract: Background and Purpose— The prevalence of silent brain infarcts varies from 8% to 28% in the general elderly population. Silent brain infarcts are associated with increased risk of subsequent stroke and cognitive dysfunction. By definition, silent strokes lack clinically overt stroke-like symptoms and fail to come to clinical attention; however, impaired recall of symptoms may be a potential confounder. Our aim is to report a series of patients with incidentally detected acute and subacute strokes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 9 publications
1
27
0
1
Order By: Relevance
“…8 Moreover, 0.92% (6/649) of subjects undergoing MRI scans for research studies in cognitive impairment had AII. 9 By contrast, the communitybased Prospective Urban Rural Epidemiological (PURE) Mind substudy recently reported no AII among 793 participants.…”
mentioning
confidence: 99%
“…8 Moreover, 0.92% (6/649) of subjects undergoing MRI scans for research studies in cognitive impairment had AII. 9 By contrast, the communitybased Prospective Urban Rural Epidemiological (PURE) Mind substudy recently reported no AII among 793 participants.…”
mentioning
confidence: 99%
“…These signs, however, are not benign at all since they are independently associated with WMH, lacunae, and subcortical atrophy, may partly be the consequence of silent strokes ''not listened to'' by both patients and physicians [59], thus probably constituting a red flag for future cognitive decline. Therefore, it is of paramount importance that these signs are not underestimated but assessed in combination with an accurate history and exhaustive imaging evaluation to prevent progression of cerebrovascular disease and future neurological and cognitive disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the "silence" of chronic microvascular brain tissue changes may be due to various reasons: lesions in non-eloquent brain areas like the frontal lobes, small lesions causing minor symptoms not recognized as stroke symptoms, the sensitivity and memory of the patient. Particularly the latter reason may have introduced a recall bias [40]. Third, as we reviewed both hemispheres (including the affected side) on brain imaging, acute ischemic lesions may have obscured chronic microvascular brain tissue changes potentially resulting in an underestimation of the extent of these lesions.…”
Section: Discussionmentioning
confidence: 99%